New genera and species of Rohrthripidae (Thysanoptera: Tubulifera) from Burmese Cretaceous amber - Ulitzka, Manfred R. (Zootaxa, 2022)
The Rohrthripidae is a family of fossil tubuliferan thrips known exclusively from the Cretaceous. Despite typical tubuliferan features, these thrips show terebrantian character states, particularly on the wings and antennae, which have been interpreted as plesiomorphic. At present, the family includes only a single genus, with seven species. In the present study, 11 new species and four new genera of these ancestral thrips are described from Burmese Cenomanian amber: Adstrictubothrips mirapterus gen. et sp. n., Gemineurothrips microcephalus gen. et sp. n., Gemineurothrips peculiaris gen. et sp. n., Paralleloalathrips bivenatus gen. et sp. n., Rohrthrips brachyvenis sp. n., Rohrthrips multihamuli sp. n., Rohrthrips pandemicus sp. n., Rohrthrips rhamphorhynchus sp. n., Rohrthrips setiger sp. n., Sesquithrips markpankowskii gen. et sp. n. and Sesquithrips rostratus gen. et sp. n. Furthermore, Alavathrips moralesi, a species from Spanish Cretaceous amber, is placed into the Rohrthripidae and its sex is reinterpreted as male. The present study, moreover, provides a tighter definition of the Rohrthripidae and a more detailed description of important character states. Finally, it is outlined why it makes taxonomic sense to distinguish Rohrthripidae from the modern Tubulifera, the Phlaeothripidae.